Masjid Jami Al-Ikhlas Sebagai Pusat Penyebaran Dan Pembinaan Islam (Studi pada Kelurahan Mandomai Kabupaten Kapuas Provinsi Kalimantan Tengah) - anthy, sury; Aulia, Siti (IAIN Palangka Raya, 2019)
The functionalization of places of worship in this case of mosques for Muslims has been experiencing a lot of development both in terms of architecture and its function for Muslim communities. One of them is the mosque in the Kapuas district of Central Kalimantan province. This study aims to describe how the process of Islamization and the role of the Jami Al-Ikhlas Mosque as a center for